Analysis of ventilation position to reduce piston effect in tunnels - Sim, Chun Han (Nanyang Technological University, 2021)
As a train moves inside a tunnel, a phenomenon known as the piston effect occurs. This effect refers to the forced movement of air flow inside a tunnel or shaft due to the movement of vehicles within. Since natural ventilation is achieved via the piston effect, external sources of power are not required to ventilate the tunnels or shafts [1]. However, the large forces, created as a result of the piston effect, act on installations around the tunnel as well as reduce passenger comfort [2]. In Singapore, the Mass Rapid Transport (MRT) System takes up 43.8% of public transport ridership [3]. With only the two oldest train lines being built above ground, the piston effect is applicable in Singapore’s context. Despite the wealth of existing literature on the piston effect, there are few properly organised sources of reliable information [1]. Furthermore, past research done on ventilation systems are either oversimplified, or have omitted the piston effect entirely. The study aims to analyse the flow field caused by the piston effect through the use of computer simulations on flow fields. The Computational Fluid Dynamics (CFD) software used is ANSYS Fluent. This software allows for the simulation of complex flow problems, while taking into account heat transfer, turbulence, as well as the flow’s reaction to the physical model, all of which are factors which can be defined by the user. As such, accurate estimations can be done without the need for physical experiments. Subsequently, measures to reduce forces caused by the piston effect are proposed. Various types of ventilation systems will first be discussed. Afterwards, appropriate simulations of a moving train will be done, where the method of dynamic meshing, a function in ANSYS Fluent requiring C-coded User-Defined Functions (UDFs), is inserted and employed. Thereafter, by varying the distance of the air inlets and outlets, the corresponding pressure and forces will be analysed. The results of the study show that using inlets spaced 4m apart provides better ventilation in tunnels. This result was obtained through the analysis of the velocity magnitude and pressure experienced at the sides of the tunnel.